How mentor teachers and emotions influence professional identity and career decisions of preservice preschool teachers - Zhang, Xinyue; Abdul Rahman, Mohd Nazri Bin; Abd Wahab, Haris Bin; Qiu, Lianying (Frontiers in Education, 2025)
This study examines how mentor teachers and teacher emotions influence the professional identity and career choices of preservice preschool teachers in Nanchang, Jiangxi Province, China. A quantitative approach was adopted, with data collected from 230 preservice preschool teachers through validated questionnaires. Structural equation modeling (SEM) was employed to examine the relationships between mentor support, teacher emotions, professional identity, and career choice. Results revealed that mentor support significantly enhanced both professional identity and career decisions, with teacher emotions serving as both mediators and moderators in these relationships. These findings underscore the critical role of mentorship and emotional experiences in shaping career readiness and professional identity, highlighting the need for teacher education programs to integrate emotional support within mentorship frameworks to better prepare preservice teachers for their future roles.